Permasalahan Subak di Daerah Pariwisata di Subak Teges, Kecamatan Ubud, Kabupaten Gianyar - DEWI, KOMANG TRI PERMATA; WINDIA, WAYAN; DIARTA, KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Subak Problems in The Tourism Area of Subak Teges of Ubud Sub-District, Gianyar Regency The rapid development of tourism in the Ubud area raises problems for local people including the condition of agriculture in the area, one of which is happening in Subak. Subak Teges is an agricultural irrigation organization located in Peliatan Village, which is influenced by tourism development. The development of tourism facilities caused problems to Subak Teges. The problem becomes a threat to the sustainability of subak. The problems arising from tourism are assessed based on three aspects including religious, social and environmental dimensions (Tri Hita Karana). The research location was in Subak Teges, Peliatan, Ubud. The purpose of this study is to describe the problem of subak in the tourism area of Subak Teges, Ubud Sub-District, Gianyar Regency. The analytical method used is qualitative descriptive analysis. The results showed that parahyangan or spiritual aspects did not experience problems. While the human aspect of pawongan and palemahan or spatial aspect have undergone problems due to the agricultural land conversion into tourism facilities. Suggestions that can be given related to the problems is that the stakeholders should enact any rules on the governance of agricultural land, it needs to cooperate with the indigenous Village of Pakraman in managing waste and the need for an intensive supervision of tourism waste.